Efektivitas Pemberian Edukasi secara Online melalui Media Video dan Leaflet terhadap Tingkat Pengetahuan Pencegahan Covid-19 di Kota Baubau: The Effectiveness of Providing Online Education through Video and Leaflet Media on the Knowledge Level of Covid-19 Prevention at Baubau City - Sabarudin; Mahmudah, Rifa’atul; Ruslin; Aba, La; Nggawu, La Ode; Syahbudin; Nirmala, Fifi; Saputri, Atika Indra; Hasyim, Muhammad Syawal (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Covid-19 is an infectious disease caused by acute respiratory syndrome coronavirus 2 (severe acute respiratory syndrome coronavirus 2 or SARS CoV-2). As of June 30, 2020, 216 countries in the world have been confirmed to have Covid-19 with a positive number of 10,117,687 and have died 502,278. Southeast Sulawesi in particular has been confirmed as of June 30, 2020, as many as 363 positive cases, 234 recovered, and 6 deaths. Meanwhile, in Baubau, there were 20 positive confirmed cases. Compliance with health protocols is believed to prevent transmission of Covid-19. Increasing knowledge through education is one of the methods used to increase compliance. This study aims to determine the effectiveness of Covid-19 prevention education through video media and online leaflets on the level of public knowledge at Baubau City. This study used a Quasi-Experiment with the approach method of The Non-Randomized Without Control Group Pretest and Posttest Design. The population is all people of Baubau City with an affordable population during the Covid-19 pandemic based on 1,600 Whatsapp group participants with a sample size of 120 people. The sampling technique used a purposive sampling method that met certain criteria. Based on the results of statistical tests with Wilcoxon, the value on the use of video media & leaflets was obtained P = 0.001 <0.05, this indicates that there is a significant difference in knowledge before and after online education. On video media P = 0.248> 0.05 showed that there is no significant difference after online education. Whereas in the media leaflet P = 0.045 <0.05 indicated that there is a significant difference after online education. In this study, video media & leaflets and leaflet media are more effectively used as education on prevention of COVID-19 online compared to video media alone.